Indexing education/training is it a factor that can improve inter-indexer consistency? - Encanto, Joenabie A. (2004)
The study sought to find out the effects of indexing education/training, controlled vocabulary and indexing tools in inter-indexer consistency. The study had fourteen respondents from the four academic libraries of Ateneo de Manila University, Central Colleges of the Philippines, Manila Central University and university of the Philippines Diliman. Results revealed that indexing is assigned even to those librarians without indexing education/training and that almost all of the indexers do not regard indexing as their main tasks in the library.